Waste identification diagrams with OEE data - Carvalho, Dinis (2014)
Existing techniques to represent production units are not very effective in representing several dimensions of production, limiting the extent to which diagnose and problem identification is accrued. Value Stream Mapping is one such technique which, although very popular among lean practitioners, exhibits a number of practical limitations. In this paper the authors present the all new Waste Identification Diagram, encompassing a number of new features and improved graphics capabilities, which makes it a feasible alternative technique to that of VSM, while extending its breath of application by integrating Overall Equipment effectiveness data into the diagrams. An example application of the WID technique to a real production unit will be presented, screening its effectiveness for diagnosing problems, measuring performance and providing key visual information and precious clues for improvement.